1963
DOI: 10.1111/j.1537-2995.1963.tb05903.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Incidence and Characteristics of Blood Donor “Reactors”

Abstract: Analysis of “reactor” and control groups of blood bank donors reveals from a statistical standpoint younger donors, particularly female, with a previous history of fainting are more prone to reaction. The “reactor” group had a tendency toward a higher pulse rate and pulse pressure and a lower diastolic pressure before bleeding. Race, blood type and body temperature did not influence the incidence of reactions. It was three times more likely for a one‐time “reactor” to have a subsequent reaction than for a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…‘Anxiety' is identified in many older studies as being associated with vasovagal reaction rates [53,54,55,56,57]. A talkative phlebotomist [58], phlebotomists with good interactive skills [59,60], a donor social support person during the donation process [61], and distraction [62,63] all reduced anxiety and decreased vasovagal rates to some extent.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
“…‘Anxiety' is identified in many older studies as being associated with vasovagal reaction rates [53,54,55,56,57]. A talkative phlebotomist [58], phlebotomists with good interactive skills [59,60], a donor social support person during the donation process [61], and distraction [62,63] all reduced anxiety and decreased vasovagal rates to some extent.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
“…Moreover, little is known about the frequency of adverse reactions during apheresis donations [18][19][20][21][22] since these procedures have been introduced only recently. Similarly, there are few recent studies attempting to determine predictive factors for donor reactions [23,24]. In the this study we analyzed all adverse events among blood and apheresis donors recorded at our transfusion center between January 1998 and June 2001.…”
Section: Introductionmentioning
confidence: 99%
“…1). It is worth noting that these percentages are comparable to figures concerning the frequency of vasovagal reactions in blood donors at other sites (Callahan et al, 1963;Ogata et al, 1980). Data analysis of responses to the vasovagal symptom questionnaire began with a factor analysis using varimax rotation.…”
Section: Resultsmentioning
confidence: 94%
“…Given the chronic difficulties in maintaining an adequate blood supply and the greater safety of blood obtained from repeat donors (Piliavin, 1990), the prediction and possible prevention of vasovagal reactions in people who would like to participate in this socially beneficial activity would be quite useful. However, while some investigators have found donor reports of past experiences to be useful (Callahan et al, 1963;Kaloupek et al, 1985), their ability to predict vasovagal episodes leaves much to be desired. This is probably due to a number of factors such as inaccurate recall, concerns about self-presentation, and, in many instances, insufficient experience with invasive medical procedures to allow a determination of one's typical response.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation